Unlocking the potential of private forests in Madhya Pradesh, India. Issue 3 (3rd July 2019) - Sushant,
ABSTRACT: Trees outside state-owned forests have the potential to meet local and national needs for timber, pulp and allied industries, reduce imports, and increase carbon sequestration. An analysis of the operation of private forestry in the state of Madhya Pradesh, India, indicates that the realization of this potential involves a liberalization of existing legislation and specified changes in regulatory procedures that at present result in delays in seeking permission to fell timber, transport it and receive payments, which cause private forest owners to lose interest in tree planting and to shift towards alternative uses of their land.